Pendekatan “Real Option” Dalam Valuasi Aset Jalan Tol Trans Sumatera - Muhammad Rifqy; Zaäfri Ananto Husodo (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Sumatra Island is the locomotive of Indonesia's economic development in the western region, so the development of the economy in Sumatra Island is one of the conditions for the sustainability of the economy in western Indonesia and the Indonesian economy in general. Therefore, if development in Sumatra Island stagnates, the development of the surrounding areas will also be hampered. In order to improve the smooth movement of goods and people and distribution on the island of Sumatra, the central government encourages the construction of the Trans Sumatra Toll Road ("JTTS"). In its implementation, the concession of JTTS is assigned to PT Hutama Karya (Persero) ("HK") through Presidential Regulation. However, JTTS is not financially feasible, so the operation of 5 (five) JTTS sections has an impact on HK's performance due to the large interest expense that must be borne by the company. One solution that can be done is to do an asset recycle or asset disposal (divestment) of JTTS that has been operating. Valuation with the real option method pays attention to the flexibility of cash flows over the volatility of the toll road business within a certain period of time expressed in binomial step nodes. With the limitation that the divestment value is at least 1 (one) time compared to the value that has been invested by the company (par value), the option to wait can assist management in making decisions to divest operating segments simultaneously within a certain period of time until it reaches a minimum par value.